Motivasi dan Partisipasi Petani Padi dalam Program Pengembangan Usaha Agribisnis Pedesaan (PUAP) di Desa Maesan - Amelia Putri Harisah (Fakultas Pertanian, 2025)
The largest contributor to poverty in Indonesia comes from rural areas. The majority of rural communities work in the agricultural sector, and many workers still live below the poverty line. One of the problems frequently faced by farmers is the limited capital available for their farming activities. The Rural Agribusiness Development Program (PUAP) serves as a means of providing business capital assistance to member farmers—whether landowners, tenant farmers, farm laborers, or farming households—coordinated through farmer groups (Gapoktan). This program was created to reduce poverty and unemployment. Maesan is one of the villages that has received capital assistance from the PUAP program since 2011, as most farmers in Maesan Village experience limited capital in managing their farming activities. The objectives of this study are to analyze the level of farmers’ motivation in the PUAP program, to analyze the level of farmers’ participation in the PUAP program, and to analyze the relationship between motivation and participation of rice farmers in the PUAP program in Maesan Village. The research location was selected purposively, namely Maesan Village. The sample was determined using a simple random sampling method. The research population consisted of 300 rice farmers who obtained capital loans from PUAP. The sample size was calculated using the Slovin formula with a 15% margin of error. This study employed a quantitative approach with descriptive and correlational methods. The data analysis method used a statistical approach, namely Likert scale scoring and correlational analysis using the Spearman rank correlation technique.
Entry oleh Arif 2026 Januari 29
Keywords: Motivation; Participation; Rural Agribusiness Development Program (PUAP)